Pengaruh Kecerdasan Emosional (EQ) terhadap Kedisiplinan Calon Imam - Benyamin Robertus Sila; Herman Punda Panda (Jurnal Teologi Berita Hidup, 2023)
The Seminary is a formation institution for priest candidates who will become reliable servants of the church. As priests, they will participate in the three duties of Christ (Tre munere Christi) namely being priests (sanctifying mankind), prophets (preaching the Word), and king/shepherd (leading the congregation). For this reason, life discipline is essential to develop four dimensions of maturity, namely personality, spirituality, intellect, and pastoral abilities. Discipline is closely related to the emotional maturity of each student. Therefore, this research aims to determine the effect of emotional intelligence on the discipline of prospective priests during their formation at the St. Mikhael Major Seminary in Kupang, East Nusa Tenggara. It applies statistical analysis techniques of Pearson Correlation Product Moment with two variables. The population amounted to 200 people with a sample of 30, which is 15% of the total. Data collection technique was in the form of a questionnaire distributed to the respondents. The data is then analyzed to describe the actual situation. Based on the results of data processing and analysis, there is a significant influence of emotional intelligence on the discipline of prospective priests at St. Michael Seminary, in a strong correlation level. Seminari adalah lembaga pembinaan calon imam yang akan menjadi pelayan gereja yang handal. Sebagai imam, mereka akan berpartisipasi dalam tiga tugas Kristus (Tre munere Christi) yaitu menjadi imam (menguduskan umat manusia), nabi (memberitakan Sabda), dan raja/gembala (memimpin jemaat). Untuk itu, disiplin hidup sangat penting untuk mengembangkan empat dimensi kedewasaan, yaitu kepribadian, spiritualitas, intelek, dan kemampuan pastoral. Disiplin erat kaitannya dengan kematangan emosi setiap mahasiswa. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pengaruh kecerdasan emosional terhadap kedisiplinan mahasiswa calon imam selama pembinaan di Seminari Tinggi St. Mikhael Kupang, Nusa Tenggara Timur. Penelitian ini menggunakan teknik analisis statistik Pearson Correlation Product Moment dengan dua variabel. Populasi berjumlah 200 orang dengan sampel sebanyak 30 orang yaitu 15% dari jumlah keseluruhan. Teknik pengumpulan data berupa kuesioner yang dibagikan kepada responden. Data tersebut kemudian dianalisis untuk menggambarkan keadaan yang sebenarnya. Berdasarkan hasil pengolahan dan analisis data, terdapat pengaruh yang signifikan dari kecerdasan emosional terhadap kedisiplinan calon imam di Seminari Tinggi St. Michael, pada tingkat korelasi yang kuat.